THE INFLUENCE OF POSITIONING AND PRODUCT DIFFERENTIATION ON INTEREST IN BUYING PT GRAHA ALUMINUM PRODUCT MEDAN - Simorangkir, Niastyna (Journal of Financial Management & Accounting, 2024)
This research was conducted at PT Graha Aluminum Product Medan Medan. The purpose of this study was to determine and analyze the influence of Positioning Pieces and Product Differentiation on Purchasing Interest of PT Graha Aluminum Product Medan. The population numbered 151 customers while the sample in this study were: 110 customers. The sampling technique used is incidental sampling. Data collection techniques are the distribution of questionnaires, interviews and documentation studies and literature studies. Data analysis uses multiple linear regression analysis. The conclusion of this research is that partially Positioning has a positive and significant effect on PT Graha Aluminum Product Medan's Interest in Buying Partially Product Differentiation has a positive and significant effect on PT Graha Aluminum Product Medan's Interest in Buying. Simultaneously Product Positioning and Differentiation have positive and significant influence on PT Graha Aluminum Product Medan's Interest in Buying. Adjusted R Square is: equal to 0.346 meaning Product Positioning and Differentiation can explain Buying Interest of 34.6% and the remaining 65.4% (100-34.6) is influenced by other variables outside of this study such as: Product Quality, Marketing Communication Marketing Strategy and so on.